Determination of Chromium and Other Metal Oxides in Chromite Ores - GIRIDHARAN, L.; VENUGOPAL, T.; JAYAPRAKASH, M. (Asian Journal of Chemistry, 2010)
A study has been carried out on the separation of silica, iron, titanium, aluminium in chromite samples and their quantitative determination using conventional as well as with atomic absorption spectrophotometry. The dissolution conditions of the minerals with HClO4 was optimized and compared with the fusion of the chromite ore with Na2O2. Perchloric acid dissolution was carried out on the reference standard samples and several chromite ores from Tamil Nadu. The recovery yields of individual metal oxides present in the mineral was found to be better than the Na2O2 fusion procedure. Good precisions were obtained for all samples and standards. The method is simple, rapid and economic and found to be ideal for the determination of iron, titanium, aluminium and silica in chromite rocks.